Contributory Roles of pH and Temperature in Phase and Morphology CaCO3 Formation Using Steamed Ammonia Liquid Waste by a Direct Carbonation - Song, Xuewen (Langmuir : the ACS journal of surfaces and colloids, 2025)
Resource utilization of waste and CO2 capture are one of the key technologies, and temperature and pH are the key factors that determine the nucleation and crystallization of CaCO3. Factors such as temperature and pH on CaCO3 production, polymorphism, and growth processes were studied using steamed ammonia liquid waste as direct carbonation. The resulting CaCO3 particles were characterized by using powder X-ray diffraction (XRD) and scanning electron microscopy (SEM). The findings demonstrated that the original CaCl2 pH and reaction temperature had a synergistic effect on the crystal-phase composition and morphology of CaCO3. The original CaCl2 pH has a strong competition on CaCO3 nucleation, crystallization, and growth process under the 40-60 °C reaction temperature. The mechanism analysis indicated different phases and morphology CaCO3 formation due to the reaction system. Ca2+, CO2-3, H+, and OH- concentration; nucleation rate; carbonation rate; calcite dissolution rate; and dissolution critical value of CaCO3 were changed by the competitive role of reaction temperature and pH. This study successfully demonstrated the selective synthesis of all the anhydrous crystalline polymorphs of CaCO3 using a unique approach